ANALISIS STRATEGI MARKETING 4C PADA BOGOR PERMAI BAKERY - Nisrina Alya Fatharani; Lingga Yuliana (Jurnal Bina Bangsa Ekonomika, 2024)
Bread is one of the alternative wheat products for staple foods in Indonesia. Unstable imported wheat prices and intense competition in the bread industry are one of the challenges for Bogor Permai Bakery. This study aims to analyze segmentation, targeting, and positioning, analyze the internal conditions of Bogor Permai Bakery based on the 4C marketing mix strategy, and formulate appropriate marketing strategy solutions based on the 4C marketing mix strategy. The research method used is field research with a qualitative descriptive research approach. The results showed that Bogor Permai has implemented a marketing strategy through segmentation, targeting and positioning analysis as well as the 4C marketing mix strategy. This research provides recommendations for the formulation of new marketing strategies based on the 4C marketing mix. The new strategy suggested in the co-creation aspect is to explore new flavors by combining two or more different flavors in one bakery product. The aspect of currency by implementing e-wallet payment methods. The communal activation aspect by introducing Bogor Permai products within the Bogor City foodie-based community, and collaborating with influencer marketing. Conversation aspect by implementing creative content through social media